2017
DOI: 10.1038/s41467-017-01883-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand break repair pathway regulates PD-L1 expression in cancer cells

Abstract: Accumulating evidence suggests that exogenous cellular stress induces PD-L1 upregulation in cancer. A DNA double-strand break (DSB) is the most critical type of genotoxic stress, but the involvement of DSB repair in PD-L1 expression has not been investigated. Here we show that PD-L1 expression in cancer cells is upregulated in response to DSBs. This upregulation requires ATM/ATR/Chk1 kinases. Using an siRNA library targeting DSB repair genes, we discover that BRCA2 depletion enhances Chk1-dependent PD-L1 upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
441
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 563 publications
(499 citation statements)
references
References 62 publications
24
441
2
3
Order By: Relevance
“…Consistent with this notion, depletion of Ku70/80 complexes enhances DSB end resection, which has been ascribed to the failure of DSB end protection, followed by increased ATR/Chk1 activation compared with that of control cells. Consistent with the increased activation of ATR/Chk1 signaling, depletion of Ku70/80 enhances further upregulation of the expression of DNA damage‐dependent PD‐L1 . Additionally, BRCA2 depletion also induces upregulation of PD‐L1 expression after DSB formation.…”
Section: Regulation Of Pd‐l1 Expression In Response To Dna Damage Sigmentioning
confidence: 68%
See 3 more Smart Citations
“…Consistent with this notion, depletion of Ku70/80 complexes enhances DSB end resection, which has been ascribed to the failure of DSB end protection, followed by increased ATR/Chk1 activation compared with that of control cells. Consistent with the increased activation of ATR/Chk1 signaling, depletion of Ku70/80 enhances further upregulation of the expression of DNA damage‐dependent PD‐L1 . Additionally, BRCA2 depletion also induces upregulation of PD‐L1 expression after DSB formation.…”
Section: Regulation Of Pd‐l1 Expression In Response To Dna Damage Sigmentioning
confidence: 68%
“…In our recent study, we found that depletion of Ku70/80 or BRCA2 significantly enhances the upregulation of PD‐L1 expression after IR . Ku70/80 and DNA‐PKcs bind to most DNA break ends immediately after the induction of DSBs (Figure ) .…”
Section: Regulation Of Pd‐l1 Expression In Response To Dna Damage Sigmentioning
confidence: 92%
See 2 more Smart Citations
“…A siRNA‐mediated screen of DSB repair genes found that loss of BRCA2 enhanced expression of PD‐L1, specifically in response to DSBs induced by IR or PARPi. Furthermore, loss of genes associated with the error‐prone NHEJ pathway, such as Ku80, substantially enhanced PD‐L1 expression in response to IR (Sato et al ., ). It was observed that treatment with IR and cisplatin significantly increased expression of PD‐L1 and that this effect was abrogated when cells were also treated with pharmacological inhibitors of ATR.…”
Section: Alternative Dna Repair‐targeting Therapies For Use In Colorementioning
confidence: 99%